Plasmonic colorimetric and SERS sensors for environmental analysis. Issue 2 (2nd April 2015) - Wei, Haoran; Hossein Abtahi, Seyyed M.; Vikesland, Peter J.
<x xml:space="preserve">Abstract</x> Plasmon based spectroscopic methods provide a novel means to detect and quantify environmentally relevant pollutants.